Technology-based change in Thai education: The one tablet per child initiative - Julien Hardy (2018)
© Common Ground, Julien Hardy and Alexander Nanni. This paper will present a case study of a recent technology-based initiative in the Thai educational system, the One Tablet Per Child (OTPC) project, which aims to provide every first grade student in the country with a tablet computer. After briefly outlining the recent history of reform in the Thai educational system and explaining the present situation, the paper will explore the implementation of OTPC. It will then evaluate this implementation in two key areas: how to deliver content and what content do deliver. The central conclusion is clear: although ambitious and well-funded, the OTPC initiative does not provide significant and lasting benefits to the kingdom's most disadvantaged students.